Coronary heart disease mortality in severe vs. non-severe familial hypercholesterolaemia in the Simon Broome Register. (February 2019) - Humphries, Steve E.; Cooper, Jackie A.; Capps, Nigel; Durrington, Paul N.; Jones, Ben; McDowell, Ian F.W.; Soran, Handrean; Neil, Andrew H.W.; ,
Abstract: Background and aims: The International Atherosclerosis Society (IAS) has proposed that patients with "severe" FH (SFH) would warrant early and more aggressive cholesterol-lowering treatment such as with PCSK9 inhibitors. SFH is diagnosed if LDL-cholesterol (LDLC) > 10 mmol/L, or LDLC >8.0 mmol/L plus one high-risk feature, or LDLC >5 mmol/L plus two high-risk features. Here we compare CHD mortality in SFH and non-SFH (NSFH) patients in the UK prospective Simon Broome Register since 1991, when statin use became routine. Methods: 2929 definite or possible PFH patients (51% women) aged 20–79 years were recruited from 21 UK lipid clinics and followed prospectively between 1992 and 2016. The excess CHD standardised mortality ratio (SMR) compared to the England and Wales population was calculated (with 95% confidence intervals). Results: 1982 (67.7%) patients met the SFH definition. Compared to the non-SFH, significantly ( p < 0.001) more SFH patients had diagnosed CHD at baseline (24.6% vs. 17.5%), were current smokers (21.9% vs 10.2%) and had a BMI > 30 kg/m 2 (14.9% vs. 7.8%). The SMR for CHD mortality was significantly ( p  = 0.007) higher for SFH (220 (184–261) (34, 134 person years, 129 deaths observed, vs . 59 expected) compared to NSFH of 144 (98–203) (15, 432 person years, 32 observed vs . 22 expected). After adjustment for traditional risk factors, the Hazard Ratio for CHD mortality in SFH vs . NSFH was 1.22 (0.80–1.87) p  = 0.36, indicating that the excess risk was largely accounted for by these factors. Conclusions: CHD mortality remains elevated in treated FH, especially for SFH, emphasising the importance of optimal lipid-lowering and management of other risk factors. Graphical abstract: Image 1 Highlights: Patients with IAS-defined "severe" FH (SFH) are at highest risk of future CHD. In the UK Simon Broome FH Register ∼70% meet the SFH criteria. Those with SFH have 64% higher CHD mortality than non SFH patients. This is explained by their higher classical risk factors including untreated LDL-C.